HAKIKAT FILSAFAT ILMU DALAM PENYELENGGARAAN PELAYANAN PUBLIK DENGAN MEMAKNAI NILAI FALSAFAH ADAT BASANDI SYARAK’, SYARAK’ BASANDI KITABULAH ( STUDI KASUS POLRES SOLOK KOTA ) - Alahan Sinaga; Azmi Fitrisia; Bobi Rizki Ananda (Ensiklopedia of Journal, 2022)
With the enactment of Law Number 25 of 2009 concerning Public Services, all local governments are trying to improve the quality of services provided. In the Act it is explained that service standards are benchmarks used as guidelines for the implementation of public services. One of the institutions that has succeeded in providing public services is the Solok City Police, this study aims to describe and analyze whether the Solok City Police in realizing its success has interpreted the philosophy of science by using the values of the traditional philosophy of basandi syarak' syarak' basandi kitaullah. This research was motivated by the Solok City Police as a Project Pilot in the implementation of public services in West Sumatra in 2019, then to see how far the Solok City Police implemented the ABS-SBK values in realizing this success, because long before the service principles were established, ABS-SBK values have long existed in public service matters. In this study, the researcher used qualitative research methods, the data that the researchers used were primary and secondary which were collected by interview, documentation and observation methods. The results of the study indicate that the Solok City Police in implementing public services have interpreted the traditional philosophy of basandi syarak' syarak' basandi Kitabullah.Keywords: Philosophy of Science, Indigenous Basandi syarak', syarak' basandi Kitabullah, Public Service